Knowledge of tuberculosis in nursing students’ university of Colombia (2015)
Objective: To identify the knowledge of Tuberculosis (TB) in nursing students from an university in Bogotá, Colombia, in period 2013-II. Materials and Method: Quantitative, descriptive and transversal study. Information was collected based on a previously developed questionnaire, consisting on 35 questions (18 of them sociodemographic and 17 testing the knowledge). Data was then processed in the statistical program SPSS Version 21, knowledge was analyzed using Spearman correlation coefficient to determine relationships. Ethical aspects of the research were preserved. Results: 119 students participated (43 of them belonging to the first three enrollments and 76 of them to the eighth enrollment onwards). Students belonging to the lasts enrollments had a higher number of hits in their responses, compared with students of the first three. There were significant differences between the groups. Using Spearman correlation coefficient and relating the enrollments with the knowledge a rho of 0,68 was obtained. Conclusions: It was found shortcomings in the knowledge related to TB between participating nursing students on issues such as the usefulness of BCG vaccine (Bacillus Calmette-Guérin), symptoms, the Directly Observed Treatment Short-Course Strategy (DOTS), treatment and drug resistance. It was considered the need to focus efforts to improve training and strengthen the knowledge.